Longitudinal associations of adherence to the Dietary World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) and Dutch Healthy Diet (DHD) recommendations with plasma kynurenines in colorectal cancer survivors after treatment - Holthuijsen, Daniëlle; Bours, Martijn J. L.; Roekel, Eline H. van; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska L. G.; Keulen, Eric T. P.; Ueland, Per M.; Midttun, Øivind; Brezina, Stefanie; Gigić, Biljana; Gsur, Andrea; Kok, Dieuwertje E.; et al. (Nutrients, 2022)
The tryptophan-kynurenine pathway has been linked to cancer aetiology and survivorship, and diet potentially affects metabolites of this pathway, but evidence to date is scarce. Among 247 stage I-III CRC survivors, repeated measurements were performed at 6 weeks, 6 months, and 1 year post-treatment. Adherence to the World Cancer Research Fund/ American Institute for Cancer Research (WCRF) and Dutch Healthy Diet (DHD) recommendations was operationalized using seven-day dietary records. ...
Gesehen am 09.11.2023